Characteristics of extreme daily precipitation events over the Canadian Arctic. (18th November 2022) - Serreze, Mark C.; Voveris, Jessica; Barrett, Andrew P.; Fox, Shari; Blanken, Peter D.; Crawford, Alex
Abstract: Given growing interest in extreme high‐latitude weather events, we use records from nine meteorological stations and atmospheric reanalysis data to examine extreme daily precipitation events (leading, 99th and 95th percentile) over Arctic Canada. Leading events span 90 mm at Cape Dyer, along the southeast coast of Baffin Island, to 26 mm at Sachs Harbour, on the southwest coast of Banks Island. The 95th percentiles range from 20 to 30% of leading event sizes. Extreme events are most common on or near the month of climatological peak precipitation. Contrasting with Eurasian continental sites having a July precipitation peak corresponding to the seasonal peak in precipitable water, seasonal cycles in precipitation and the frequency of extremes over Arctic Canada are more varied, reflecting marine influences. At Cape Dyer and Clyde River, mean precipitation and the frequency of extremes peak in October when the atmosphere is quickly cooling, promoting strong evaporation from Baffin Bay. At all stations, leading events involved snowfall and strong winds and were associated with cyclone passages (mostly of relatively strong storms). They also involved strong vapour fluxes, sometimes associated with atmospheric rivers or their remnants. The most unusual sequence of events identified here occurred at Clyde River, where the three largest recorded precipitation events occurred in April of 1977. Obtaining first‐hand accounts of this series of events has proven elusive. Identified links between extreme events and atmospheric rivers demonstrates the need to better understand how the characteristics of such features will change in the future. Abstract : As is evident from patterns of vertically integrated water vapour transport (IVT), extreme precipitation events in Arctic Canada, such as that which occurred at Cape Dyer on January 1980, are often associated with atmospheric rivers or the remnant of them.